Survey on decentralized security-enhanced technologies for RPKI - QIN Chaoyi; ZHANG Yu; FANG Binxing (Tongxin xuebao)
The resource public key infrastructure (RPKI) deploys a centralized and hierarchical infrastructure for the authorization of IP addresses. It not only enhances the security of the Internet border gateway protocol system, but also introduces centralization into the routing system. According to the functions of the certificate authorities, the authorization center, operation center, and publication center in the RPKI were proposed, and a comprehensive survey on decentralized security-enhanced technologies for the RPKI were presented based on these three centers. Firstly, RPKI centralization risks were refined from the perspective of authorization, operation and publication. Secondly, the technical ideas and solutions of decentralized security-enhanced technologies were classified into these three perspectives. Thirdly, technologies were compared in terms of security, scalability, and incremental deployment. Finally, the existing problems in current technologies were summarized and the future research directions were prospected.